Το δικαστικό προνόμιο της Νέας Μονής Χίου - ΟΙΚΟΝΟΜΙΔΗΣ, Ν. (Byzantina Symmeikta, 1997)
Nikos Oikonomides The Judicial Privilege of Nea Moni on Chios Emperor Constantine IX Monomachos granted (1045) to the monastery of Nea Moni on Chios a judicial privilege: any action against the monastery should be brought to court in front of the imperial tribunal only (JGR I, 629-631). In the present article it is argued that this privilege has nothing to do with the western immunitas, because the privilege does not give the monastery any right to judge other people. The privilege is compared to the similar ones granted to the monasteries of Lavra (963-964) and Iviron (1079). And it is interpreted as an effort to protect the founders of Nea Moni, who were seemingly spiritual mysticists, from the monastic establishment of Constantinople, especially the cenobitic Stoudiou movement. In fact, as we learn from Psellos, the founders of Nea Moni were eventually accused and condemned of heresy by the imperial tribunal under empress Theodora (1055-56), but were later re-instated thanks to the support of Patriarch Michael Keroularios.